Optimizing The Role Of Bumdes In Improving The Economy Of The Gelangsar Village Community - Zain, Irma Istihara; Maulana, Bayu Aftiar; Kurniawan, Alan; Aspuri, Aspuri; Abdi, Lalu Pradifta Putra; Sari, Diana Laela (Abdi Masyarakat, 2024)
Introduction: The development of villages and underdeveloped areas has long been on the government's agenda as a national development goal because villages are a real target that must be prosperous and rural areas still dominate poverty in Indonesia. Objective: To optimize the role of BUMdes in improving the economy of the Gelangsar village community. Problem Formulation: How to optimize the role of Bumdes in improving the community's economy and what are the factors for the failure of Bumdes in improving the economy of the Gelangsar village community. Research Method: This research was conducted using descriptive qualitative methods. Results: It is undeniable that the existence of BUMDes has brought changes in the economic and social fields. BUMDes' contribution is mainly in the form of Village Original Income, where BUMDes net profits are allocated to Village income and the ability of BUMDes to develop and function as expected depends on the basic material and social assets (both tangible and intangible) owned. Conclusion: The existence of BUMDes brings significant changes in the economic and social fields. Shifts in social values and also changes in interaction patterns between citizens will occur. BUMDes provides an increase in Village Original Income, but this income cannot be felt directly by the community.